DETERMINANTS OF DIABETES MELLITUS PREVALENCE IN INDONESIA: A MULTIPLE LINEAR REGRESSION MODEL IN AN ECOLOGICAL ANALYSIS OF ADULTS AGED 15 YEARS AND OLDER - Nuridzin, Dion Zein; Aghram, Nauval; Mawarni, Atik; Retnowati, Retnowati (Jurnal Manajemen Kesehatan Indonesia, 2024)
Indonesia faces a double burden of disease, with an increasing prevalence of non-communicable diseases (NCDs), such as diabetes mellitus (DM), alongside communicable diseases. This study investigates the determinants of DM prevalence among individuals aged 15 years and older in Indonesia. An ecological design was employed using secondary data from the 2018 Basic Health Research Report, 2018 Welfare Statistics Report, and the 2019 Provincial in Figures Report, encompassing 514 districts across 34 provinces. Data analysis included univariate descriptive statistics, Pearson correlation for bivariate analysis, and multiple linear regression with a backward method to identify significant predictors. The results revealed significant associations between DM prevalence and hypertension (p < 0.001), obesity (p < 0.001), routine blood sugar testing (p < 0.001), good nutrition (p = 0.016), the ratio of general hospitals (p < 0.001), public health centers (p < 0.001), and physicians (p < 0.001), as well as the interaction between hospital and physician ratios (p < 0.001). The model explained 61.5% of the variance in DM prevalence (R² = 0.615), meeting all multiple linear regression assumptions. Prevalence of hypertension, obesity, and higher ratios of general hospitals and physicians were positively correlated with DM prevalence, while good nutrition and greater availability of public health centers exhibited protective effects. The positive association of routine blood sugar testing likely reflects increased screening in high-DM areas. These findings highlight the need for targeted public health interventions, emphasizing obesity reduction, nutritional improvements, and equitable healthcare distribution to mitigate DM prevalence in Indonesia.